IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF BERBASIS GIVING QUESTION AND GETTING ANSWER (GQGA) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS IV MI WAHID HASYIM 02 DAU, MALANG. - Elianata Ningtyas; lia Nur Atiqoh Bela Dina; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study seeks to present the implementation of learning strategies based on Giving Question and Getting Answer in improving student learning outcomes.  The objectives of this study are: To describe the planning of learning strategies based  on giving questions and getting answers in improving student learning outcomes in mathematics learning at MI Wahid Hasyim 02 Dau Malang;  To describe the implementation of learning strategies based  on giving questions and getting answers in improving student learning outcomes in mathematics learning at MI Wahid Hasyim 02 Dau Malang;  To describe the evaluation of learning strategies based  on giving questions and getting answers in improving student learning outcomes in mathematics learning at MI Wahid Hasyim 02 Dau Malang.  The results showed that: planning action was carried out in sufficient detail starting from the preparation of instruments in the form of observation sheets for the implementation of teacher learning, observation sheets for student activities, and test sheets used to measure student learning outcomes;  evaluation of student activities is related to the weakness of the Giving Question and Getting Answer  strategy which is difficult to distinguish the learner's questions whether he does understand the material or does not understand the material.Keywords: implementation, mathematic, teacher learning, learning strategies.